Synthesis and reactivity of 7,9-diphenyl-nido-carbaundecaboranes: Rearrangement processes in carbaplatinaboranes revisited - Welch, A; Weller, A (1997)
A number of synthetic routes towards diphenyl nido-carbaborane [7,9-Ph2-7,9-nido-C2B9H10] - have been elucidated. Base-induced degradation of 1,7-Ph2-1,7-closo-C2B10H10 afforded two isolable products [NEt3H]-[7,9-Ph2-x-OEt-7,9-nido-C2B 9H9] (x = 3 1a or 2 1b), both of which contain an ethoxide-substituted cage. The structural identity of 1a was established by a single-crystal X-ray diffraction study. Fluoride-induced degradation gave a product assigned as [NBu4][7,9-Ph2-10-OH-7,9-nido-C2B 9H9] 2, also studied crystallographically. Heating a solid sample of Cs[7,8-Ph2-7,8-nido-C2B9H10] in a sealed tube under vacuum for 4 h at 300°C afforded the target species [NEt3H][7,9-Ph2-7,9-nido-C2B9H 10] 3, after cation metathesis. Deprotonation of 3 and reaction with [PtCl2(PMe2Ph)2] afforded the new compound 1,1-(PMe2Ph)2-2,4-Ph2-1,2,4-closo-PtC 2B9H9 4. Compound 4 has been characterised by multinuclear (1H, 11B and 31P-{1H}) NMR spectroscopy as well as a single-crystal X-ray diffraction study. The isolation of this stable (in refluxing toluene) compound having a 1,2,4-MC2B9 cage architecture indicates that a hextuple-concerted diamond-square-diamond mechanism cannot be operating in the spontaneous isomerisation of 1,2-Ph2-3,3-(PMe2Ph)2-3,1,2-closo-PtC 2B9H9 below ambient temperature to afford 1,1-(PMe2Ph)2-2,8-Ph2-1,2,8-closo-PtC 2B9H9. The new compounds 1,1-(PR3)2-2,4-Ph2-7-OEt-closo-1,2,4-PtC 2B9H8 (R3 = Me2Ph 5a or Et5 5b), both fully characterised by multinuclear NMR spectroscopy, have also been synthesized.